(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study was conducted in the urgent housing complex in Mather (Riyadh) as a partial requirement to obtain a master’s degree in risk management. The study was about the risks in the urgent housing complex in Mather and its effects on engineering projects. This study aimed to identify the risks in the urgent housing complex in Al-Mather and their effects on engineering projects, and the extent to which the reduction of those risks was achieved. To achieve these goals, the researchers collected information from reliable sources from the previous study, and by means of a questionnaire for the purpose of collecting real data from the workers in the complex as well as the supervisors in the complex with a variety of experiences from the private and public sectors and contractors. The questions of the questionnaire included the effects of risks on engineering projects, focus on maintenance, construction and general services in the complex, and strategies to reduce those risks. The study concluded with results indicating the general services that are implemented in the complex with a general average of (3.17) according to the five-point Likert scale, and with an average standard deviation of (1.39) for the first axis. The results showed agreement on the impact of risks on maintenance work with a general average of (2.9) with an average standard deviation of (1.45) for the second axis, and the results also showed that the sample agrees on the impact of risks on the implementation of construction projects with a general average of (3.18) and an average standard deviation of (1.17) for the third axis. The study recommended the operation of safety systems and reducing the risk of leakages that affect the safety of buildings, the creation of a department specialized in risk management and treatment, as well as the allocation of budgets for maintenance and new projects to maintain the devices and components of the project for the development and modernization of the complex and to keep pace with the current regulations in the Kingdom of Saudi Arabia.